ANALISA PENGARUH JUMLAH TANGGUNGAN KELUARGA TERHADAP PENDAPATAN PEKERJA PT. INHUTANI I SEI TUBU MALINAU - Devi, Charitin; Sabariah, Nur (Ekonomi Pembangunan Fakultas Ekonomi, 2024)
This study aims to determine the effect of the number of family dependents on production labor income at PT Inhutani I Sei Tubu Malinau. The data used in this study are primary data obtained through questionnaires distributed to production workers at PT Inhutani I Sei Tubu Malinau. The sample in this study amounted to 30 respondents, the analytical tool used was simple linear regression. The results of this study that partially (t test), shows that the number of family dependents, affects income with R2 of 0.6329 this shows that 67.6% of income can be explained by the number of family dependents, while the remaining 32.4% is influenced by other independent variables that have not been included in the research model